A Density Functional Theory of a Nickel-based Anode Catalyst for Application in a Direct Propane Fuel Cell - Vafaeyan, Shadi (Université d'Ottawa / University of Ottawa, 2012)
The maximum theoretical energy efficiency of fuel cells is much larger than those of the steam-power-turbine cycles that are currently used for generating electrical power. Similarly, direct hydrocarbon fuel cells, DHFCs, can theoretically be much more efficient than hydrogen fuel cells. Unfortunately the current densities (overall reaction rates) of DHFCs are substantially smaller than those of hydrogen fuel cells. The problem is that the exchange current density (catalytic reaction rate) is orders of magnitude smaller for DHFCs. Other work at the University of Ottawa has been directed toward the development of polymer electrolytes for DHFCs that operate above the boiling point of water, making corrosion rates much slower so that precious metal catalysts are not required. Propane (liquefied petroleum gas, LPG) was the hydrocarbon chosen for this research partly because infrastructure for its transportation and storage in rural areas already exists. In this work nickel based catalysts, an inexpensive replacement for the platinum based catalysts used in conventional fuel cells, were examined using density functional theory, DFT. The heats of propane adsorption for 3d metals, when plotted as a function of the number of 3d electrons in the metal atom, had the shape of a volcano plot, with the value for nickel being the peak value of the volcano plot. Also the C-H bond of the central carbon atom was longer for propane adsorbed on nickel than when adsorbed on any of the other metals, suggesting that the species adsorbed on nickel was less likely to desorb than those on other metals. The selectivity of the propyl radical reaction was examined. It was found that propyl radicals
Keywords: Density Functional Theory; Anode Catalyst; Direct Propane Fuel Cell; SIESTSA; Nickel